Experimental study of droplet formation in the cross-junction. Issue 8 (14th June 2021) - Wu, Suchen; Chen, Juan; Liu, Xiangdong; Yao, Feng
Abstract: The dynamic formation characteristics of droplets in a cross-junction can be captured via a high-speed image setup. The experimental results show four flow regimes: slug, dripping, jetting (threading and tubing), and viscous displacement. When Cad and Cac are small, the slug regime occurs. The dripping regime occurs when Cac is relatively high. The jetting regime appears when Cad increases to a considerable value. When Cac is much smaller than Cad, the viscous displacement regime occurs. In the slug and dripping regimes, the dispersed phase will experience growing, squeezing, and pinching off stages in the formation of droplets. These four flow regimes are strongly affected by Cac and Cad . In addition, the flow rates of the two phases can be changed to adjust the sizes of the generated droplet in the cross-junction under the slug regime and dripping regime. The dimensionless droplet length l * can be predicted via l * = (0.248 + 0.55 Q )Cac −0.203 . Graphical Abstract: